EVALUASI PELAKSANAAN PROGRAM MINAPOLITAN TAHUN 2009-2011 DI KABUPATEN BANYUMAS - ono, Rudi; Harsasto, Priyatno; Taufiq, Ahmad (Journal of Politic and Government Studies, 2014)
Minapolitan program, is a national government program implemented to encourage thedevelopment of aquaculture in the region to improve the economy and growth of aquacultureactivities. One of the districts that have implemented Minapolitan Program Year 2009 isBanyumas. The development of aquaculture production of fish rearing quite rapidly from 2009-2011. Production continued to rise although not yet able to meet production targets in 2010 and2011. However, the conditions found in the field of fisheries issues Agribusiness system fromupstream to downstream is not optimal, especially in the area of marketing and processing.This type of research uses descriptive analysis , with research sites in Pokdakan Mina Sari , SariUlam Pokdakan I and Mina Bieber as Pokdakan receiver Minapolitan Program to illustrate whyit has not happened yet understanding / seriousness related local government offices in theachievement of program implementation Minapolitan . In addition, the analysis also illustrateshow the process of program implementation Minapolitan?The results showed that there were some problems in the process of implementing the programMinapolitan as in planning, development, and management. The process of planning, does notalways involve the community in planning programs, because that is representative of the peopleinvolved and the results are not planning to convey to the general public. So that people onlyknow of three Pokdakan program planning of components and labor costs contributed to thedevelopment of facilities and infrastructure Minapolitan program. On the other hand, MinaPokdakan Bieber has problems in infrastructure development programs impacting Minapolitanimplementation Minapolitan program management, which is a problem in the process ofdetermining the source of water that does not go through trials so that the adequacy of the waterproduced is not sufficient for the community to irrigate the pond, which in turn making facilitywas never used and is not maintained by the community. Mina Pokdakan Ulam Sari Sari and Ihave a problem in the irrigation development process that hampered the development processtimeline completion. Resulting in stagnating water supply to the pond .Keywords: Minapolitan program, process, community involvement